Heart rate variability and cortisol levels before and after a brief anaerobic exercise in handball players - Kayacan, Y.; Makaraci, Y.; Uçar, C.; Amonette, W. E.; Yildiz, S. (The Journal of Strength and Conditioning Research, 2023)
Evaluating stress in athletes is important for monitoring overall physiologic load and is a core practice for sport performance teams. This study examined relationships between 2 metrics of training stress, heart rate variability (HRV) and cortisol, before and after intense anaerobic power testing. Electrocardiogram recordings and saliva samples were collected before and immediately after a Wingate anaerobic power test (WAnT-30) from professional handball players (n = 20) and sedentary controls (n = 18). Between-group differences and correlations were computed to assess study hypotheses. No differences were observed in HRV frequency-dependent parameters between groups, but in athletes, Min. R-R (p < 0.01) and Avg.R-R (p = 0.03) before WAnT-30 and the percentage of successive normal cardiac beat intervals greater than 50 milliseconds (i.e., pNN50; p = 0.03) after WAnT-30 were elevated. A high positive correlation was detected between the pretest and post-test cortisol levels in athletes (p = 0.0001; r = 0.87) but not in sedentary individuals. No correlations were observed between the cortisol levels and WAnT-30 power parameters in either group. Relationships were evident in the standard deviation of RR intervals (p = 0.02, r = -0.53), square root of the mean squared difference of successive RR intervals (p = 0.043, r = -0.46), very low frequency (p = 0.032; r = -0.480), high-frequency (p = 0.02; r = -0.52) variables, and pretesting cortisol in athletes. These findings suggest that HRV analysis is a valuable tool for examining cardiovascular regulation, independent of cortisol; the data may provide valuable information for performance teams in evaluating acute stress.